Epilepsy in South Sudan: practical guidelines for better control - Peter Maketh Makuei; Mohammed Boy Sebit; William Howlett; Marieke Dekker (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
Epilepsy is usually a chronic condition. In many regions of the world care is compromised by limited recognition, access to medication and stigma. Quality of life for people with epilepsy and their families can improve substantially when seizures are recognised and better control instituted with the appropriate medication. Recognition and classification of seizures, coupled with evidence-based and rational pharmacological management, can help resolve the many issues around this chronic neurological condition.